2022
DOI: 10.1186/s43170-022-00099-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breeder seed multiplication and certified quality seed distribution on rice production in India

Abstract: Background The All India Coordinated Rice Improvement Project (AICRIP) organizes multi-location tests (METs) with new genotypes from breeding programs. The best performing genotypes in METs for 3–4 years are identified and notified as commercial cultivars by the Government of India (GOI) to authorize breeder seed (BS) production. Methods We created a database and analyzed data on BS production for 24 years (1995–96 to 2018–19) in 475 inbred and 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Breeder seed production is vital for maintaining the long-term seed chain and is the prime responsibility of public sector institutions and agencies ( Vishnu et al., 2013 ; Prasad et al., 2022 ). The Indian seed program recognizes three generation system: breeder, foundation, and certified seeds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Breeder seed production is vital for maintaining the long-term seed chain and is the prime responsibility of public sector institutions and agencies ( Vishnu et al., 2013 ; Prasad et al., 2022 ). The Indian seed program recognizes three generation system: breeder, foundation, and certified seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed that BS indent has reduced by 85.58% from 1998–1999 to 2021–2022. However, increasing trends of BS demand have been reported in food crops like wheat ( Krishna et al., 2016 ), rice ( Prasad et al., 2022 ), barley ( Vishnu et al., 2013 ), and pulses ( Parihar and Dixit, 2016 ). There might be few probable but imperative reasons that could explain the declining lucerne BS demand in the country such as (1) shifting of cultivated lucerne area into different fodder crops, (2) disparity in BS production and demand, (3) unrealistic and extremely high BS demand by the indenters, (4) extensive efforts of private seed companies in seed production and direct selling to the farmers, and (5) presence of the unorganized seed sector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to develop upland rice are faced with the problem of providing good quality seeds. Testing the quality and quality of seeds is very important because these tests can assure farmers that to avoid losses incurred during cultivation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%